2019
DOI: 10.26666/rmp.ijbm.2019.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Military Leaders' Leadership Styles and Subordinates Hardiness Level: Can Transformational and Transactional Leadership Influence Soldier’s Hardiness?

Abstract: In comparison with the western military setting, the absence of the study of leadership styles and personality hardiness in the Malaysian Army (MA) has been noticeable. Personality hardiness of the soldiers', and whether military transformational and transactional leadership provides a significant impact on soldier's hardiness level, is critical in a modern military environment in facing many unique challenges, due to the increase of forward deployment rate. As such, the present study examines the proposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…The effective leader provides help to subordinates in clarifying roles and reconciling incompatibilities, makes available time and resources, and supports organizational initiatives to minimize tensions (Hersey & Blanchard, 1993). Studies report that transformational leadership can increase military resilience (Jayasingam et al, 2019) by positively reinterpreting stressful experiences as opportunities for personal growth and development (Bartone, 2012). Resilient leaders encourage soldiers to see stressful experiences as challenges and learning opportunities, having a positive impact on the group they belong to (Țiclău et al, 2021).…”
Section: The Role Of External Resources: Management Style and Perceiv...mentioning
confidence: 99%
See 1 more Smart Citation
“…The effective leader provides help to subordinates in clarifying roles and reconciling incompatibilities, makes available time and resources, and supports organizational initiatives to minimize tensions (Hersey & Blanchard, 1993). Studies report that transformational leadership can increase military resilience (Jayasingam et al, 2019) by positively reinterpreting stressful experiences as opportunities for personal growth and development (Bartone, 2012). Resilient leaders encourage soldiers to see stressful experiences as challenges and learning opportunities, having a positive impact on the group they belong to (Țiclău et al, 2021).…”
Section: The Role Of External Resources: Management Style and Perceiv...mentioning
confidence: 99%
“…Public safety workers' perceptions of organizational structure and climate can directly affect resilience (Hart & Cooper, 2001). It has been shown that transformational leadership can increase military resilience (Jayasingam et al, 2019) by positively reinterpreting stressful experiences as opportunities for personal growth and development (Bartone, 2012). Also, studies demonstrate the effectiveness of psychological training activities in the sense of increasing resilience (Arnetz et al, 2013).…”
mentioning
confidence: 99%